SOC Для виробників автомобілів - Пятайкіна, М. І.; Васильєв, Ю. С.; Горбенко, Є. О.; Карнаушенко, В. П. (ХНУРЕ, 2022)
There are many factors to consider when auto OEMs decide whether to go with a customized SoC or ―off-the-shelf‖ products. Some questions include whether the car is intended for a broad-based market with little differentiation from others, which key IP should be brought in-house versus relying on external providers, and what are the trade-offs in terms of power, performance, size and costs. In the end, automotive vendors must decide what is most suitable to them, based on the options available.